Development of a Testlet Model Physics Learning Assessment to Know Students' Cognitive Profiles on Static Fluids - Afifah, Rachma; Marwoto, Putut; Ellianawati, Ellianawati (Physics Communication, 2021)
The ability of students to achieve learning objectives can be measured by conducting an assessment. There are various forms of assessment, and the assessment in the form of a testlet is believed to have advantages in identifying the students' conceptual understanding achievements. This study aims to develop a testlet model physics instrument that is valid, reliable, and feasible to use. The development procedure used is 4D which consists of 4 stages, namely: Define, Design, Develop, and Disseminate. However, this research is reduced to 3D only limited to the Develop stage. The research was conducted in a high school located in the city of Semarang. The small-scale trial sample involved 20 students who were selected using a random sampling technique. The results showed that the content validity analysis by the expert obtained an average result of 0.9 in the valid category. The results of the small-scale product test analysis showed that 92% of the items were declared valid and 8% of the items were declared invalid. The question is declared to have very high reliability with a value of 0.974. Analysis of the level of difficulty obtained criteria for 8% difficult questions and 92% moderate questions. The discriminating power of the questions shows the percentage of 2% of the questions being rejected, 2% of the questions being corrected, 2% of the questions being accepted well with improvements, and 94% of the questions being well-accepted.